EFFECT OF FREE ALKALOID AND NON-FREE ALKALOID ETHANOL 70% EXTRACT OF JUSTICIA GENDARUSSA BURM F. LEAVES AGAINST REVERSE TRANSCRIPTASE HIV ENZYME IN VITRO AND CHEMICAL COMPOUND ANALYSIS - Prajogo, Bambang; Widiyanti, Prihartini; Riza, Hafrizal (Indonesian Journal of Tropical and Infectious Disease, 2016)
HIV-AIDS is a global problem and the deadliest disease in the world. One of HIV and AIDS prevention strategy can be done with traditional medicine research program from natural resource that has anti-HIV AIDS activity. It has been found that 70% ethanol extract of Justicia gendarussa Burm.f leaves, alkaloid free and alkaloid non-free, has a strong inhibitory activity against HIV reverse transcriptase enzyme, as an effort to find a solution in the face of HIV AIDS prevalence that is still high with problem of HIV-AIDS treatment such as side effects and resistances. Justicia gendarussa had already known for having an effect anti-HIV and therefore we were looking at the mechanism of inhibition of HIV Reverse Transcriptase enzyme. Both types of extracts were tested in vitro using ELISA technique and analysed chemical content of Gendarusin A as anti-HIV using high performance liquid chromatography. ELISA test results obtained percent inhibition, respectively for 254.2, 254.2, 235.6, and 279.7 for the concentration of 5 ppm, 10 ppm, 15 ppm and 20 ppm of free alkaloid extract and 169.0, 164.0, 130.5 and 369.5 for the concentration of 5 ppm, 10 ppm, 15 ppm and 20 ppm of non-free-alkaloid extract. The results of high performance liquid chromatography obtained Gendarusin A in the free alkaloid extract at retention time 8.402 minutes and non-free alkaloid extract at retention time 8.381. Therefore, these results concluded that the Justicia gendarussa Burm.f can be a useful resource for the isolation and development of new anti-HIV.